2022
DOI: 10.1088/1757-899x/1234/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Study of parameter affecting morphology of electrospun poly (lactic acid) (PLA) fibers loaded with Ag/CaCO3 filler

Abstract: Silver nanoparticles (AgNPs) are widely used as antimicrobial agent in commercial products like textiles, cosmetics and drugs. AgNPs deposited on the surface of calcium carbonate (CaCO3) particles, serve as sustained release of antimicrobial activity. The silver nanoparticles embedded calcium carbonate particles (Ag/CaCO3) are prepared by a precipitation method. In this study, precipitated (Ag/CaCO3) filler will be used for preparation of Ag/CaCO3-poly(L-lactic acid) (Ag/CaCO3-PLA) nanofibers by electrospinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The CaCO 3 aggregation was confirmed by detecting clusters of CaCO 3 with a higher number of CaCO 3 particles inside the beads compared to the rest of the fibers (Figure 9). 49 In addition, the higher number of beads in 8% CaCO 3 -RG and 3% CaCO 3 -RG fibers compared to the RG PVC confirmed the effect of CaCO 3 and viscosity on the bead formation. The centrifuged PVC pipe fibers showed a lower number of beads compared to all the CaCO 3 -containing samples, which confirmed that the removal of CaCO 3 by centrifugation resulted in less bead formation.…”
Section: Fiber Characterizationmentioning
confidence: 67%
See 3 more Smart Citations
“…The CaCO 3 aggregation was confirmed by detecting clusters of CaCO 3 with a higher number of CaCO 3 particles inside the beads compared to the rest of the fibers (Figure 9). 49 In addition, the higher number of beads in 8% CaCO 3 -RG and 3% CaCO 3 -RG fibers compared to the RG PVC confirmed the effect of CaCO 3 and viscosity on the bead formation. The centrifuged PVC pipe fibers showed a lower number of beads compared to all the CaCO 3 -containing samples, which confirmed that the removal of CaCO 3 by centrifugation resulted in less bead formation.…”
Section: Fiber Characterizationmentioning
confidence: 67%
“…The stretching force to elongate the solution is represented by the charge density on the electrospinning jet. Inadequate charge density causes insufficient elongation viscosity to counteract Rayleigh instability, resulting in the formation of beads. , Also, additives might affect the bead formation based on their solubility in the solvent. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the results from the antimicrobial study showed that the films have bacteriostatic effects on Salmonella Enteritidis and Listeria Monocytogenes bacteria. In another similar study, the silver nanoparticles were embedded in calcium carbonate particles (Ag/CaCO 3 ) by a precipitation method and further loaded in poly (L-lactic acid) nanofibers by electrospinning technique with potential usage for antimicrobial food adsorbent pads application (Zin and Sutapun, 2022). This is worthy of mentioning that all of the research works available in the literature reported the chemical or physical treatment methods to reduce the size or modify eggshell particles to decrease the surface tension between eggshell particles and polymer matrix.…”
Section: Polymer Bio-filler Compositementioning
confidence: 99%